Monitoring cellular uptake and cytotoxicity of copper(II) complex using a fluorescent anthracene thiosemicarbazone ligand - Kate, Anup N.; Kumbhar, Anupa A.; Khan, Ayesha A.; Joshi, Pranaya V.; Puranik, Vedavati G. (Bioconjugate Chemistry, 2014)
The thiosemicarbazone derivative of anthracene (ATSC, anthracene thiosemicarbazone I) and its copper(II) complex (CuATSC, 2) were synthesized and characterized by spectroscopic, electrochemical, and crystallographic techniques. Interaction of 1 and 2 with calf thymus (CT) DNA was explored using absorption and emission spectral methods, and viscosity measurements reveal a partial-intercalation binding mode. Their protein binding ability was monitored by the quenching of tryptophan emission using bovine serum albumin (BSA) as a model protein. Furthermore, their cellular uptake, in vitro cytotoxicity testing on the HeLa cell line, and flow cytometric analysis were carried out to ascertain the mode of cell death. Cell cycle analysis indicated that 1 and 2 cause cell cycle arrest in sub-G1 phase.